Comparison of treatment outcome using two definitions of rapid cycling in subjects with bipolar II disorder - Amsterdam, Jay D (Bipolar Disord, 2017)
OBJECTIVES: We examined differences in treatment outcome between DSM-IV defined rapid cycling and average lifetime defined rapid cycling in subjects with bipolar II disorder. We hypothesized that the average lifetime definition of rapid cycling may better identify subjects with a history of more mood lability and a greater likelihood of hypomanic symptom induction during long-term treatment. METHODS: Subjects ≥18 years old with bipolar II major depressive episode (n = 129) were categorized into DSM-IV and average lifetime definition of rapid cycling and prospectively treated with either venlafaxine or lithium monotherapy for 12 weeks. Responders (n = 59) received continuation monotherapy for six additional months. RESULTS: These exploratory analyses found moderate agreement between the two rapid cycling definitions (κ = 0.56). The lifetime definition captured subjects with more chronic courses of bipolar II depression, whereas the DSM-IV definition captured subjects with more acute symptoms of hypomania. There was no difference between rapid cycling definitions with respect to response to acute venlafaxine or lithium monotherapy. However, the lifetime definition was slightly superior to the DSM-IV definition in identifying subjects who went on to experience hypomanic symptoms during continuation therapy. CONCLUSIONS: Although sample sizes were limited, the findings suggest that the lifetime definition of rapid cycling may identify individuals with a chronic rapid cycling course and may also be slightly superior to the DSM-IV definition in identifying individuals with hypomania during relapse-prevention therapy. These findings are preliminary in nature and need replication in larger, prospective, bipolar II studies.